Genome-wide association analyses define pathogenic signaling pathways and prioritize drug targets for IgA nephropathy - Kiryluk, Krzysztof; Sanchez-Rodriguez, Elena; Zhou, Xu Jie; Zanoni, Francesca; Liu, Lili; Mladkova, Nikol; Khan, Atlas; Marasa, Maddalena; Zhang, Jun Y.; Balderes, Olivia; Sanna-Cherchi, Simone; Bomback, Andrew S.; et al. (Nature Genetics, 2023)
IgA nephropathy (IgAN) is a progressive form of kidney disease defined by glomerular deposition of IgA. Here we performed a genome-wide association study of 10,146 kidney-biopsy-diagnosed IgAN cases and 28,751 controls across 17 international cohorts. We defined 30 genome-wide significant risk loci explaining 11% of disease risk. A total of 16 loci were new, including TNFSF4/TNFSF18, REL, CD28, PF4V1, LY86, LYN, ANXA3, TNFSF8/TNFSF15, REEP3, ZMIZ1, OVOL1/RELA, ETS1, IGH, IRF8, TNFRSF13B and FCAR. The risk loci were enriched in gene orthologs causing abnormal IgA levels when genetically manipulated in mice. We also observed a positive genetic correlation between IgAN and serum IgA levels. High polygenic score for IgAN was associated with earlier onset of kidney failure. In a comprehensive functional annotation analysis of candidate causal genes, we observed convergence of biological candidates on a common set of inflammatory signaling pathways and cytokine ligand–receptor pairs, prioritizing potential new drug targets.
CRIS-Team Scopus Importer:2023-06-30